Implementation of E-Comics to Grow Environmental Literacy using Outdoor Learning Methods in the New Normal Time - Brian Priyangga; Sarwi Sarwi; Arif Widiyatmoko (Eduvest - Journal of Universal Studies, 2022)
The implementation of e-comic development is based on the low level of environmental literacy due to the lack of training and incomplete material in the textbook, so that students are not accustomed to being skilled in carrying out environmental literacy in the surrounding environment, especially during the COVID-19 pandemic and in inclusive education. The research method in this article is a systematic literature review. The purpose of developing e-comic is to produce learning media used independently by students to foster environmental literacy in grade 4 Elementary School. This environmental literacy hopes that students can achieve goals such as: (1) Awareness (increasing individual awareness, and sensitivity to the environment), (2) Knowledge (gaining experience in gaining a basic understanding of the environment), (3) Attitude (increasing feelings and values of caring for the environment, as well as motivation to actively participate in environmental protection), (4) Skills (increasing skills to solve environmental problems), (5) Participation (actively involved in the community in efforts to solve environmental problems). The achievement of problem-solving skill competencies can also help students to support other skills such as reading and writing. In addition, it also applies a project-based learning model. This is because there is a problem that problem solving abilities are still low, so a Project Based Learning model is needed